Analisis Sistem Akuntansi Prosedur Pembayaran Klaim Jaminan Hari Tua Pada Badan Penyelenggara Jaminan Sosial Ketenagakerjaan Cabang Meulaboh - Era Wati; Rina Maulina (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
BPJS Employment provides protection for all formal and informal sector workers as well as foreigners who work in Indonesia for a minimum of 6 months. Currently, most of the people in Meulaboh Aceh Barat work in the formal sector to meet their financial needs. This research was conducted to determine the accounting information system for payment of JHT claims at the BPJS Employment office in the Meulaboh branch. Old age insurance claims are not only made by workers who are laid off, but also by workers who make claims during the pandemic. The accounting system in terms of the JHT payment steps at the BPJS Ketenagakerjaan office of the Meulaboh Branch has been carried out correctly starting from the bound function, the documents used, the accounting records used, and the procedures in the form of the accounting system. However, there is a problem in the claim submission procedure, namely the participant who attaches an account book that is already passive or in a period of respite, so that the claim process takes time.